A study of initial 251 Covid-19 patients admitted at Government Medical College, Kota - Sardana, Vijay; Singhal, Govind (International Journal Of Community Medicine And Public Health, 2020)
ABSTRACT Background: A new strain of Corona virus, presently known as Covid-19, belongs to the family of Corona viruses that originated in animals, has not previously been identified in humans. The high infectivity of the disease led to the third Corona virus outbreak in the last 20 years after the SARS-CoV and the Middle East respiratory syndrome MERS-CoV. Methods: It was a hospital based descriptive cross-sectional study at GMC, Kota Hospital, conducted from 5 April to 10 May 2020. All the positive patients who were residents of Kota and diagnosed and admitted at Government Medical College (GMC), Kota were selected for this study. A pretested and structured questionnaire was used. Data were entered, processed and analyzed using SPSS version 20. Results: Out of total 251 included patients, 162 Males and 89 Females. The most affected containment zones were Chandraghata, Suket, Bhimganjmandi and Anantpura. The mass Sampling was satisfactory in Chandraghata, Bhimganjmandi and Anantpura. Seventy one percent of first follow up sample were negative which was increased on subsequent follow up sample. Only 10 Patients died with the case fatality rate of 03.98%. Twenty five percent patients became follow up positive even though their first follow up sample was negative. Conclusions: Males were more affected then females. Maximum number of cases belonged to 20-50 years of age. Sampling pattern was not uniform. The results do not justify labelling to the asymptomatic/mild Covid-19 positive patient as cured just after the first follow up negative. Most common co-morbidities in fatal Covid-19 patients were diabetes mellitus, hypertension and chronic obstructive pulmonary disease.